Electrophile Signaling and Emerging Immuno- and Neuro-modulatory Electrophilic Pharmaceuticals - Poganik, Jesse R.; Aye, Yimon (Frontiers in Aging Neuroscience, 2020)
With a lipid-rich environment and elevated oxygen consumption, the central nervous system (CNS) is subject to intricate regulation by lipid-derived electrophiles (LDEs). Investigations into oxidative damage and chronic LDE generation in neural disorders have spurred the development of tools that can detect and catalogue the gamut of LDE-adducted proteins. Despite these advances over the century, deconstructing the precise consequences of individual protein-specific LDE-modifications remained largely impossible until recently. In this perspective, we first overview emerging toolsets that can decode electrophile-signaling events in a protein/context-specific manner, and how the accumulating mechanistic insights brought about by these tools have begun to offer new means to modulate pathways relevant to multiple sclerosis (MS). By surveying the latest data surrounding the blockbuster MS drug dimethyl fumarate that functions through LDE-signaling-like mechanisms, we further provide a vision for how chemical biology tools probing electrophile signaling may be leveraged toward novel interventions in CNS disease.